Gender differences in child health: evidence from the demographic and health surveys - Upchurch, D. M.; Hill, Kenneth H.
tbls., gráfs.
pp. 127-151
Keywords: Mortalidad Infantil; Aspectos Sanitarios; Oriente Medio